The impact of economic growth on CO2 emissions in East Asian and North African Countries during the period 1990-2020 using the CS-ARDL model - Mebrek, Nacer; Louail, Bilal (International journal of economic perspectives, 2024)
Using the CS-ARDL model, this study examines how economic growth affects CO2 emissions in East Asian and North African nations between 1990 and 2020. Control variables like population size, trade openness, GDP per capita, and power use are included in the analysis. The results show a strong long-term cointegrating link between CO2 emissions and economic growth. There is a clear correlation between rising economic growth and rising power consumption and rising CO2 emissions over the long run, with the latter having a greater impact. Population size and trade openness have less of an association with CO2 emissions. The outcomes exhibit resilience against multiple empirical obstacles, such as autocorrelation, heteroskedasticity, and model misspecification. Diagnostic checks verify the validity of the CS-ARDL estimations and the stability of the long-run parameters. The study offers crucial insights into the connection between environmental impact and economic growth, arguing that energy consumption and economic aspects should be considered in CO2 emission reduction programs.